KSPPS Development Strategy for Bina Ummat Sejahtera to Improve the Welfare of Cooperative Members - Rachmania Yusa Afriani; Shela Saskia Pradya Paramita; Futihah Roudhoturizki (International Journal of Entrepreneur and Business Administration, 2024)
This article examines the implementation of development strategies by KSPPS BMT Bina Ummat Sejahtera in improving member welfare through sharia financial services. Using qualitative methodology, this research evaluates the influence of adequate infrastructure, innovation in services, and human resource development on members' economic empowerment. The results show that adopting a holistic approach to cooperative operations—including improving the accessibility and efficiency of financial services as well as training programs to improve members' financial competency—significantly supports member empowerment and community economic growth. This initiative not only strengthens members' financial stability but also stimulates inclusive economic growth in the community. This study confirms that KSPPS BMT Bina Ummat Sejahtera has been effective in forming an ethical financial ecosystem and supporting the economic independence of its members.